Fractional differintegral operators of the generalized Mittag-Leffler function - Anjali Gupta; C. L. Parihar (Boletim da Sociedade Paranaense de Matemática, 2015)
The Riemann-Liouville and Erdélyi-Kober operators of fractional integrals and derivatives,those were generalized by Saigo, are invoked to the generalized Mittag-Lefflerfunction. Some apparent particular cases are mentioned